Lipid Profile Features and Their Associations With Disease Severity and Mortality in Patients With COVID-19 - Sun, Jia Teng; Chen, Zhongli; Nie, Peng; Ge, Heng; Shen, Long; Yang, Fan; Qu, Xiao Long; Ying, Xiao Ying; Zhou, Yong; Wang, Wei; Zhang, Min; Pu, Jun (Frontiers in Cardiovascular Medicine, 2020)
Abstract Background: Emerging studies described and analyzed the epidemiological, clinical, laboratory, and radiological features in COVID-19 patients. Yet, scarce information is available regarding the association of lipid profile features and disease severity and mortality. Methods: We conducted a prospective observational cohort study to investigate the lipid profile features in patients with COVID-19. From February 9 to April 4, 2020, a total of 99 patients (31 critically ill and 20 severely ill) with confirmed COVID-19 were included. The dynamic alteration of the lipid profile was recorded and tracked. Outcomes were followed up until April 4, 2020. Results: We found that high-density lipoprotein-cholesterol (HDL-C), apolipoproteinA-1 (apoA-1) levels were significantly lower in the severe group, with the dead cases holding the lowest levels (p<0.0001). Furthermore, HDL-C (OR: 0.012, 95%CI: 0.000-0.372, p=0.012) and apoA-1 (OR: 0.014, 95%CI: 0.000-0.479, p=0.018) were independently associated with the severity of the disease. And AUC of admission HDL-C and apoA-1 for predicting severe condition were 0.78 [95% CI, 0.70–0.85] and 0.85 [95% CI, 0.76–0.91], respectively. For in-hospital death, HDL-C and apoA-1 held similar discriminability with the AUC of 0.75 [95% CI, 0.61–0.88], and 0.74 [95%CI, 0.61–0.88], respectively. Moreover, patients with lower serum apoA-1 (<0.95g/L) or HDL-C (<0.84mmol/l) had higher mortality rate during hospitalization (log-rank P <0.001). Notably, the initial decreased apoA-1/HDL-C levels in severe-survivors recovered since hospitalized day 35, while in non-survivors apoA-1/HDL-C constantly deteriorated throughout the clinical course. Correlation analysis revealed that apoA-1 and HDL-C negatively correlated with both the admission and the highest concentration of C-reactive protein and Interleukin-6. Conclusions: Severe COVID-19 patients featured low HDL-C and apoA-1 levels, which strongly correlated with the inflammatory states. Low apoA-1 and HDL-C levels might be promising predictors for severe condition and in-hospital mortality in patients suffering from COVID-19.